1986
DOI: 10.1557/proc-73-165
|View full text |Cite
|
Sign up to set email alerts
|

Silicon −29 Solids NMR-MAS Characterization of Non-Oxide Powders and Fibers

Abstract: Powder x-ray diffraction has been the most common method for rapid structural analysis and identification of crystalline ceramic raw materials.However, new structural ceramic raw materials often have linebroadened or featureless XRD patterns due to structural strain or small crystallite size. Characterization of various silicon carbide and silicon nitride powders and ceramic fibers by Si-29 NMR-MAS spectroscopy has revealed structural details and differences in these materials previously indistinguishable by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…From the 29 Si NMR spectra it follows that during the heat treatment of the starting gels at 400 ³C, the less condensed units (T 1 , T 2 and Q 3 ) condense further thus resulting, as expected, in more completely condensed T 3 and Q 4 units and a higher degree of condensation. This trend of increasing condensation as a function of temperature was also found to continue in the samples heat treated at 600 ³C.…”
Section: (I)supporting
confidence: 68%
See 4 more Smart Citations
“…From the 29 Si NMR spectra it follows that during the heat treatment of the starting gels at 400 ³C, the less condensed units (T 1 , T 2 and Q 3 ) condense further thus resulting, as expected, in more completely condensed T 3 and Q 4 units and a higher degree of condensation. This trend of increasing condensation as a function of temperature was also found to continue in the samples heat treated at 600 ³C.…”
Section: (I)supporting
confidence: 68%
“…DTA±TG studies under synthetic air showed that the removal of ±CH 3 groups begins around 400 ³C in such gels containing colloidal silica 24 and thus this temperature was chosen as the upper temperature for the heat treatment in air. 29 Si NMR spectra of the samples, containing 0 or 0.25 mol of colloidal silica per mol of alkoxide, heat treated at 400 ³C in air (type A) or nitrogen atmosphere (type N), are shown in Fig. 3.…”
Section: (I)mentioning
confidence: 99%
See 3 more Smart Citations